2014
DOI: 10.1539/joh.13-0146-br
|View full text |Cite
|
Sign up to set email alerts
|

Skill Underutilization is Associated with Higher Prevalence of Hypertension: The Watari Study

Abstract: Skill Underutilization is Associated with Higher Prevalence of Hypertension: the Watari Study: Satoshi KONNO, et al. Preventive Medical Center and Division of Hypertension, Tohoku Rosai Hospital— Objectives The aim of this study was to investigate the association between skill underutilization, a psychological job stressor proposed in the NIOSH (National Institute for Occupational Safety and Health) job stress model, and the prevalence of hypertension. Methods We studied sitting blood pressure and fasting bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
2
0
2
Order By: Relevance
“…On the other hand, another model for evaluating job stress is the National Institute for Occupational Safety and Health (NIOSH) job stress model 37 ) , where underutilization of skills is proposed as a job stressor that can elicit stress reaction. Earlier studies have shown that skill underutilization is associated with increased risk for depressive symptoms 38 ) and hypertension 39 ) . Therefore, skill utilization may act as a resource or stressor, and in this newly developed Chinese version of the new BJSQ, it may be linked to job demand, unlike the Japanese version.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, another model for evaluating job stress is the National Institute for Occupational Safety and Health (NIOSH) job stress model 37 ) , where underutilization of skills is proposed as a job stressor that can elicit stress reaction. Earlier studies have shown that skill underutilization is associated with increased risk for depressive symptoms 38 ) and hypertension 39 ) . Therefore, skill utilization may act as a resource or stressor, and in this newly developed Chinese version of the new BJSQ, it may be linked to job demand, unlike the Japanese version.…”
Section: Discussionmentioning
confidence: 99%
“…Par exemple, une méta-analyse révèle que les employés qui se perçoivent surqualifiés pour leur emploi sont moins performants au travail et moins engagés, et ils rapportent un niveau de bien-être psychologique moindre (Harari et al, 2017). De plus, une étude a même montré un lien significatif entre la sous-utilisation des compétences au travail et l'apparition de certains problèmes de santé physique comme l'hypertension et les troubles cardiaques (Konno et Munakata, 2014).…”
Section: Ce Que L'on Sait Sur L'arrimage De La Gestion De La Performaunclassified
“…Hubungan variabel kemampuan yang tidak digunakan dengan stres kerja diperoleh nilai p-value 1,000 (p-value > 0,05), dapat disimpulkan tidak ada hubungan antara kemampuan yang tidak digunakan dan stres kerja. Hasil ini berbeda dengan hasil penelitian yang dilakukan pada pekerja di Jepang didapatkan hasil bahwa kemampuan pekerja yang tidak digunakan dengan baik dapat meningkatkan risiko stres kerja yang berdampak pada peningkatan kadar tekanan darah (Konno & Munakata, 2014).…”
Section: Analisa Bivariatunclassified